2019
DOI: 10.1096/fj.201900841r
|View full text |Cite
|
Sign up to set email alerts
|

AMPK promotes induction of the tumor suppressor FLCN through activation of TFEB independently of mTOR

Abstract: AMPK is a central regulator of energy homeostasis. AMPK not only elicits acute metabolic responses but also promotes metabolic reprogramming and adaptations in the long‐term through regulation of specific transcription factors and coactivators. We performed a whole‐genome transcriptome profiling in wild‐type (WT) and AMPK‐deficient mouse embryonic fibroblasts (MEFs) and primary hepatocytes that had been treated with 2 distinct classes of small‐molecule AMPK activators. We identified unique compound‐dependent g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 87 publications
(130 reference statements)
0
53
0
Order By: Relevance
“…AMPK is also activated by phosphorylation of two regulatory subunits by several kinases, including the energy stress-sensitive LKB [214], PKA [215], and the CAMM-GSK3β axis [216] as well as by other factors, including PPARα, associated with lipid metabolism [217] and hypoxia [218]. AMPK triggers the expression of antioxidant enzymes, notably HO-1, through Nrf2 [219,220], and improves the control of proteostasis [221] through direct activation of FOXO3 [222] and ULK1 [223] and by indirect activation of TFEB [224]; AMPK activation also improves both glucose metabolism by favoring GLUT4 translocation to the membrane [225,226] and lipid metabolism through PPARα. Finally, AMPK activation results in inhibition of mTORC following both direct phosphorylation and phosphorylation of the mTORC controller TSC [227].…”
Section: Metabolic Homeostasismentioning
confidence: 99%
“…AMPK is also activated by phosphorylation of two regulatory subunits by several kinases, including the energy stress-sensitive LKB [214], PKA [215], and the CAMM-GSK3β axis [216] as well as by other factors, including PPARα, associated with lipid metabolism [217] and hypoxia [218]. AMPK triggers the expression of antioxidant enzymes, notably HO-1, through Nrf2 [219,220], and improves the control of proteostasis [221] through direct activation of FOXO3 [222] and ULK1 [223] and by indirect activation of TFEB [224]; AMPK activation also improves both glucose metabolism by favoring GLUT4 translocation to the membrane [225,226] and lipid metabolism through PPARα. Finally, AMPK activation results in inhibition of mTORC following both direct phosphorylation and phosphorylation of the mTORC controller TSC [227].…”
Section: Metabolic Homeostasismentioning
confidence: 99%
“…For example, in MPTP-treated mice, metformin treatment prevented dopaminergic cell death and reduced motor impairment while decreasing α-synuclein aggregation, autophagic impairment, and ROS (82). The possible mechanism of this effect is not clear but may involve activation of AMPactivated protein kinase (AMPK) through the mitochondrial effects of metformin which in turn leads to an induction of autophagy involving in part, autophagosome formation and lysosomal biogenesis (101)(102)(103)(104). Support for a role of AMPK comes from a study in MPTP-treated mice where downstream effectors of AMPK prevented dopaminergic cell death and motor impairment (105).…”
Section: Autophagymentioning
confidence: 99%
“…In support of this, we showed that AMPK and mTOR phosphorylation were signi cantly affected by pre-treatment with BAPTA-AM and STO609, indicating activation of the AMPK pathway and inhibition of the mTOR pathway via Ca 2+ in ux following α7 nAChR activation. In addition, AMPK phosphorylation activates TFEB, which is a potential key transcription for autophagy induction upon its dephosphorylation and nuclear translocation [43]. It has been reported that under stress conditions or upon loss of function, TDP43 can regulate the nuclear translocation of TFEB in order to promote the transcription of autophagic genes.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that α7 nAChR activation potentially induces autophagy via Ca 2+ in ux and signaling through the AMPK and mTOR pathways. α7 nAChR agonist promotes lysosomal biogenesis via nuclear translocation of transcription factor EB (TFEB) AMPK signaling activates transcription factor EB (TFEB), which is a potential key transcription in the induction of autophagy upon its dephosphorylation and nuclear translocation [43]. TFEB can enter the nucleus and bind to the E-box of the CLEAR element, which regulates the transcription of genes associated with the biogenesis of lysosomes and autophagosomes [44].…”
Section: The α7 Nachr Agonist Exerts Neuroprotective Effects Againstmentioning
confidence: 99%